The application of electrical resistivity imaging technique in the assessment of strength parameters of residual soil derived from granitic rocks - Maruthaveeran, Ugantharan (2000)
This thesis reports on the result of an empirical study to use electrical resistivity imaging technique in the assessment of ultimate shear strength of residual soil derived from the weathering product of granitic rock and to identify the depth and lateral extent of possible slip surface of sloping ground located in granitic terrain. Soil samples were taken from the field and its petrophysical, resistivity and shear strength properties were studied in laboratory. In the field, both electrical resistivity imaging survey and ultimate shear strength probing have been carried out. The result of cross-correlation between ultimate shear strength and resistivity from laboratory and field investigation were integrated to obtain a relationship, which was applied to determine the ultimate shear strength of residual soil from the electrical resistivity inversion data obtained from the study area. The residual soil was derived from the weathering of granitic rock along Kuala Kubu Bahru - Bukit Fraser federal road.Soil classification results show that the soil at the study area comprised of mainly clayey sand soil of high plasticity index. This study shows that the formation factor, x (i.e the resistivity without the influence of solution salinity in the soil) and the shear strength, y was related by an equation y = 12.347x0.5641. The present work also shows that this relationship could only be applied for soil at moisture content between 10% and 50%. The result' of field survey and 2-D subsurface imaging, also indicate that the depth of the sliding surface of the failed slope surface was about 1m - 1.5m below ground surface. The boundary between the translated and intact soil was at the ultimate shear strength of about 200kPa. Therefore it is possible to estimate the ultimate shear strength of the residual soil and to predict the depth and lateral extent of the possible slip surface using electrical resistivity imaging survey at lower cost and wider coverage of survey area.